Translation and validation study of the Bahasa Malaysia version of Lower Extremity Functional Scale (LEFS) in Hospital Tengku Ampuan Afzan, Kuantan, Pahang - Muhammad Ariff bin Mohd Yunus (Kulliyyah of Medicine, International Islamic University Malaysia, 2016)
Objective: This study was designed to produce a reliable and validated Bahasa Malaysia version of the Lower Extremity Functional Scale (LEFS). Methods: A two stage observational study was conducted. The LEFS was initially cross-culturally adapted to Bahasa Malaysia through double forward and backward translation. The finalized version of Bahasa Malaysia LEFS (BM-LEFS) was subsequently validated for the psychometric characteristics of factor analysis, criterion validity, construct validity, and reliability. Participants (n = 208) with normal lower limb condition and various lower limb conditions completed the BM-LEFS. Results: Reliability of BMLEFS revealed excellent Cronbach‟s alpha values of 0.98. Cronbach‟s alpha values of each of the 20 items, if deleted, remain high between 0.97 to 0.98. Construct validity, evaluated using confirmatory factor analysis, had good factor loadings of 0.62 and more. Analysis done based on the Varimax rotation extracted 2 components from the 20 items in LEFS questionnaire, which was not mentioned by the original author of LEFS. Conclusions: The BM-LEFS had admirable psychometric properties among the tested population. Further studies are needed to verify these preliminary outcomes in other Malaysian subjects.